Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

Comparative analysis of multiple machine learning models: identifying impact factors in biochar heavy metal adsorption mechanisms - Zixin Zeng; Yingdong Wu; Wenjie Li; Lei Han; Huangshiyu Zhao; Rong Teng; Han Yuan; Ziang Wang; Sijia Li (Environmental Geochemistry and Health, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)